Impact of the accreditation process of the career of Dentistry at Universidad Nacional Mayor de San Marcos Part I: students - Chein-Villacampa, Sylvia (2015)
To evaluate the impact of the international accreditation process at Universidad Nacional Mayor de San Marcos’s Faculty of Dentistry was the purpose of the investigation. Methodology: The study was descriptive, cross-sectional and retrospective. The sample was made up by 307 (of 450) students randomly selected. The data collection was obtained by a questionnaire survey. Chi square test (SPSS 20) was applied. The results showed that the level of student’s satisfaction related to accreditation process was regular to good (37.1% and 51.3%). About the dimensions of coherence of the achievements the purposes: relevance, integrity and effectiveness were considered as good 74.9% (p = 0.004); about the availability, efficiency and effectiveness of resources as regular 50.2% and good 34.2% (p = 0.00); with regard to changes in the process: mode of operation of the organizational structures and administrative procedures as good with 54.7% (p = 0.00) and changes in the academic process as good with 58.9% (p = 0.00). Conclusions: Students perceived that the impact after the accreditation in relation to the coherence of the achievements for the purposes of the Dentistry career and, the changes in the academic processes were predominantly good, in all years of study, except in the availability, efficiency and effectiveness of resources that were considered as fair. The level of satisfaction regarding to accreditation was ‘good’.